Using Training Program Within Specific Areas and Its Effect On Developing Physical Aspects of Youth Soccer Players - Abdul Hussein, Mohammed; Hussein, Naser (Journal of Physical Education, 2016)
The importance of the research lies in using training within specific areas todevelop physical aspects using proper aids to coordinate between physical and skill trainingin soccer. The aim of the research is to identify the effect of special exercises on thedevelopment of physical aspects in the subjects of the research.The researchers hypothesized statistical differences between experimental andcontrolling group in the posttests. The researchers used the experimental method. The pilotstudy was conducted followed by pretested then the posttests. The data was collected usingproper statistical methods. The results showed that training within specific areas led to thedevelopment of skill and physical abilities in soccer. Finally the researcher recommendedconcentrating on developing physical abilities using short and middle distance exerciseswhile specifying their frequency, time and rest according to the players' needs so as toperform the best tactics and techniques during the game.